Establishment of an Efficient In Vitro Regeneration Protocol for Rapid and Mass Propagation of Dendrobium chrysotoxum Lindl. Using Seed Culture - Potshangbam Nongdam; Leimapokpam Tikendra (The Scientific World Journal)
An efficient in vitro regeneration protocol from seed culture has been established successfully for Dendrobium chrysotoxum, an epiphytic orchid having tremendous ornamental and medicinal values. Seed germination response was encouraging in Mitra (M) medium enriched with different combinations of auxins and cytokinins. Medium supplemented with 0.4% activated charcoal (AC), 2 mg/L 6-benzyl amino purine (BAP), and 2 mg/L indole-3-acetic acid (IAA) produced best seed germination percentage in 2 weeks of culture. Incorporation of higher concentration of kinetin (KN) or BAP in combination with low auxin in medium induced pronounced shooting and leaf formation. Reduction in leaf development was evident when cytokinins exist singly in medium indicating synergistic effect of auxin and cytokinin in leaf induction. Presence of elevated level of indole-3-butyric acid (IBA) or 1-naphthalene acetic acid (NAA) with low cytokinin content in medium generated more in vitro rooting, though IBA was found to be more effective in rooting induction as compared to NAA. The in vitro protocol for asymbiotic seed germination developed from the present investigation can be used for rapid mass propagation of this highly important Dendrobium orchid species.